Preoperative Low-Molecular-Weight Heparin Prophylaxis Associated with Increased Heparin Resistance Frequency in On-Pump Coronary Artery Bypass Graft Surgery - Onur Saydam; Mehmet Atay; Deniz Serefli; Suat Doganci; Ulas Kumabasar; Mustafa Yılmaz; Rıza Dogan; Metin Demircin (Cardiology Research and Practice)
Background. Unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) are being used for preoperative management of critical coronary artery disease. However, preoperative UFH therapy may cause a reduction in antithrombin concentrations, leading to various degrees of heparin resistance (HR). The main purpose of this study is to investigate the effects of preoperative LMWH on HR during cardiopulmonary bypass (CPB). Methods. Data were retrospectively reviewed from adult patients that underwent on-pump coronary artery bypass graft (CABG) surgery. Four hundred fifty-seven patients underwent CABG, and 139 of them, who had isolated on-pump CABG, were included in the study. The heparin sensitivity index was calculated if activated clotting time levels were discovered below 400 seconds. Values less than 1.3 were accepted as HR. Results. Of 139 patients who underwent on-pump CABG, preoperative LMWH was administered in 59 patients (56.8%). Intraoperative HR occurred in 29 patients (20.9%). Patients who received preoperative LMWH had an increased risk of developing HR compared with patients who did not receive LMWH (odds ratio 4.8 and 95% confidence interval 1.7–13.5). CPB duration and aortic clamp duration were significantly longer in patients who developed intraoperative HR when compared to those in patients who did not develop HR. Conclusion. Preoperative treatment with LMWH may cause intraoperative HR. Corrective and preventive arrangements with close follow-up should be performed in this group of patients.